2020
DOI: 10.1021/acs.energyfuels.9b03648
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Sulfur Forms on Gas-Phase Mercury Removal by SO2-Impregnated Porous Carbons

Abstract: Due to widespread global mercury pollution via anthropogenic activities such as coal combustion and its severe toxicity even at low concentrations, it is necessary to remove mercury from power plant flue gas to protect both humans and the ecosystem. Currently, significant efforts are being made to maximize Hg 0 adsorption rates while minimizing the impact on the cost of electricity. The purpose of this study is to explore the influence of different sulfur forms on vapor Hg 0 removal by SO 2 -impregnated porous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…In addition, the partial additive of FeS was oxidized as Fe 2 (SO 4 ) 3 . As shown in Table 2 , combined with the mercury removal performance, both activated HSPCs modified by S and FeS had a good agreement with the previous conclusion of affinity with mercury that compared with sulfide and sulfate, elemental sulfur, sulfoxide, and sulfone have more positive effects on mercury removal [ 32 ]. In addition, Reddy et al [ 58 ] pointed out that CuS-doped carbon had a higher Hg 0 removal performance of 23 mg/g compared to that of FeS-doped carbon, which was attributed to better dispersion of active phase (CuS), lower diffusional resistance for mercury, and also activity of active phase.…”
Section: The Effect Of the Evolution Of Functional Groups On Hg ...supporting
confidence: 83%
See 2 more Smart Citations
“…In addition, the partial additive of FeS was oxidized as Fe 2 (SO 4 ) 3 . As shown in Table 2 , combined with the mercury removal performance, both activated HSPCs modified by S and FeS had a good agreement with the previous conclusion of affinity with mercury that compared with sulfide and sulfate, elemental sulfur, sulfoxide, and sulfone have more positive effects on mercury removal [ 32 ]. In addition, Reddy et al [ 58 ] pointed out that CuS-doped carbon had a higher Hg 0 removal performance of 23 mg/g compared to that of FeS-doped carbon, which was attributed to better dispersion of active phase (CuS), lower diffusional resistance for mercury, and also activity of active phase.…”
Section: The Effect Of the Evolution Of Functional Groups On Hg ...supporting
confidence: 83%
“…Considering the mercury adsorption reactivity rank that PC–NS > PC–S > PC–SC, the TPD result suggested that various sulfur species played different thermal stability when that affected Hg 0 adsorption capacity. In addition, She et al [ 32 ] found that compared with nonoxidized and oxidized sulfur forms, the reduced sulfur forms showed a rather significant correlation with the mercury adsorption performance of SO 2 -impregnated samples. Furthermore, Reddy et al [ 57 ] reported that sulfonated carbons are a potential candidate for Hg 0 removal due to their –SO 3 H groups.…”
Section: The Effect Of the Evolution Of Functional Groups On Hg ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The observed reduction in mercury reemission was likely due to the capture of oxidized or elemental mercury by sulfur. The enhanced affinity of sulfur-impregnated sorbents for the removal of both elemental and ionic mercury from the gas or liquid phase is well known. …”
Section: Resultsmentioning
confidence: 99%
“…Although some research has been carried out on preparing activated petroleum coke for mercury adsorption through SO 2 impregnation, more work is needed to fully understand the influence of different inserted sulfur forms on Hg 0 adsorption characteristics. A previous study of our group has reported that the nonoxidized sulfur is much more effective for Hg 0 uptake than oxidized sulfur . Then, the objective of this study is to identify the impact of reduced sulfur, sulfide sulfur, and elemental sulfur formed during SO 2 activation on Hg 0 adsorption.…”
Section: Introductionmentioning
confidence: 97%